Cote d'Ivoire : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Cote d'Ivoire. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Cote d'Ivoire's Requests for Disbursement Under the Rapid Credit Facility (RCF) and Purchase Under the Rapid Financing Instrument (RFI). The government's response to the pandemic has been swift, with strong social distancing and containment measures and an emergency health plan supported by the World Health Organization. The coronavirus disease 2019 pandemic is expected to have a considerable negative impact on Cote d'Ivoire's economy, creating fiscal pressures and an urgent balance of payments need. The authorities swiftly adopted strong containment measures which, while necessary, will also weigh on economic activity. In view of the severity of the pandemic, the envisaged temporary widening of the fiscal deficit is appropriate, even if this means temporarily breaching the 3 percent regional convergence criterion. Given the substantial downside risks, additional spending reallocations would be needed if tax revenue were to underperform compared to the current projection. The IMF emergency support under the RCF and RFI is expected to help the authorities address the urgent fiscal and balance of payments financing needs. It will also help catalyze additional financing from other development partners. Additional donor support is critical to close the remaining financing gap and preserve Cote d'Ivoire's substantial development gains over the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet